Nuclear Morphology Measurements with Angle-Resolved Low Coherence Interferometry For Application To Cell Biology And Early Cancer Detection - Adam Wax; Kevin J. Chalut (Analytical Cellular Pathology)
The study of intact, living cells using non-invasive optical spectroscopic methods offers the opportunity to assess cellular structure and organization in a way that is not possible with commonly used cell biology imaging techniques. We have developed a novel spectroscopic technique for diagnosing disease at the cellular level based on using low-coherence interferometry (LCI) to detect the angular distribution of scattered light. Angle-resolved LCI (a/LCI) combines the ability of LCI to isolate scattering from sub-surface tissue layers with the ability of light scattering spectroscopy to obtain structural information on sub-wavelength scales. In application to examining cellular structure, a/LCI enables quantitative measurements of changes in the size and texture of cell nuclei. These quantitative measurements are characteristic of different pathological states. The capabilities of a/LCI were demonstrated using a clinical system that can be applied in endoscopic surveillance of esophageal tissue, producing high sensitivity and specificity for detecting dysplastic tissues in vivo. Experiments with in vitro cell samples also show the utility of a/LCI in observing structural changes due to environmental stimuli as well as detecting apoptosis due to chemotherapeutic agents.